Israeli pediatricians’ confidence level in diagnosing and treating children with skin disorders: a cross-sectional questionnaire pilot study - Andre, Nicolas; Muallem, Liezl; Yahav, Lior; Golan-Tripto, Inbal; Shmuel, Atar Ben; Horev, Amir (Frontiers in Medicine, 2023)
Background: Pediatricians daily see large numbers of patients with skin disorders. However, they encounter limited guidance as a result of a marked deficiency in pediatric dermatologists.Hence, reevaluation of training opportunities during pediatric residency has become essential.Our aim was to evaluate the confidence level of pediatric residents and specialists in diagnosing and treating skin disorders in children and to determine career and training-related characteristics that influence it. Methods: Conducted as a cross-sectional study, we administered a questionnaire to 171 pediatricians across Israel. We assessed respondents' selfefficacy about their ability to diagnose and treat skin disorders and collected data regarding their previous dermatology training and preferred training methods. Results: 77.8% of respondents reported below or average self-efficacy scores in diagnosing and managing children with skin disorders. Older age (>40 years old) (OR=5.51, P=0.019), treating a higher number of patients with skin disorders (OR=2.96, P=0.032), and having any training in dermatology, either during medical school or residency (OR=7.16, P=0.031, OR=11.14, P=0.003 respectively), were all significant parameters involved in pediatricians reporting high self-efficacy in skin disorder management. Conclusions: Most pediatric residents and pediatricians have average or below-average confidence in managing pediatric skin disorders.We suggest incorporating dermatology rotations during pediatric residency to improve young pediatricians' self-efficacy in managing skin disorders and ultimately help pediatricians provide better care for patients presenting with dermatological conditions. These findings can ultimately help refine a pilot program in dermatology that might be implemented during pediatric residency.